2018
DOI: 10.1021/acscatal.8b01960
|View full text |Cite
|
Sign up to set email alerts
|

Manganese-Catalyzed β-Alkylation of Secondary Alcohols with Primary Alcohols under Phosphine-Free Conditions

Abstract: Manganese­(I) complexes bearing a pyridyl-supported pyrazolyl-imidazolyl ligand efficiently catalyzed the direct β-alkylation of secondary alcohols with primary alcohols under phosphine-free conditions. The β-alkylated secondary alcohols were obtained in moderate to good yields with water formed as the byproduct through a borrowing hydrogen pathway. β-Alkylation of cholesterols was also effectively achieved. The present protocol provides a concise atom-economical method for C–C bond formation from primary and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(57 citation statements)
references
References 58 publications
1
56
0
Order By: Relevance
“…They have utilized 0.1 mol % catalytic loading for their reaction and hence our catalysts Ru1 – Ru2 were found to be more effective compared to the catalysts reported by Kundu and co‐workers . However, our catalysts were observed to be less effective than Ru‐NHC based catalyst (0.0001 mol %) reported by the above group …”
Section: Resultsmentioning
confidence: 47%
“…They have utilized 0.1 mol % catalytic loading for their reaction and hence our catalysts Ru1 – Ru2 were found to be more effective compared to the catalysts reported by Kundu and co‐workers . However, our catalysts were observed to be less effective than Ru‐NHC based catalyst (0.0001 mol %) reported by the above group …”
Section: Resultsmentioning
confidence: 47%
“…The major challenge is that the alkylation of secondary alcohols with primary alcohols often leads to mixtures of the β‐alkylated alcohols and the β‐alkylated ketones, presenting a tricky selectivity issue (Scheme ) . Very recently, Kempe, Rueping, Yu, and co‐workers reported the β‐alkylation of secondary alcohols with primary alcohols to provide β‐alkylated alcohols using Mn complexes (Scheme b). On the other hand, the β‐alkylation of secondary alcohols with methanol to provide β‐methylated alcohols using Mn complexes were also reported by Leitner, Kempe, and co‐workers .…”
Section: Methodsmentioning
confidence: 99%
“…However, at the outset of this work, the alkylation of secondary alcohols using/from primary alcohols by Mn catalysis was not known to the best of our knowledge. During the preparation of this Communication a related parallel study was reported by Yu and co‐workers . Here, we demonstrate that the Mn–PNN pincer complex Mn‐1 is a remarkably active and selective catalyst for the alkylation reaction of alcohols (Scheme )…”
Section: Methodsmentioning
confidence: 99%